Impact of absolute lymphocyte count upon admission to ICU on 28-day mortality in sepsis patients in ICU - Zhong, DingJun; Zhao, Ling (Frontiers in Immunology, 2026)
BackgroundSepsis is associated with high mortality and poor prognosis in critically ill patients, posing a severe threat to global public health. The first absolute lymphocyte count (FALC) upon admission to the ICU, reflecting the initial state of the immune system, has emerged as a potential prognostic indicator in various critical illnesses. However, its specific role and predictive value in assessing 28-day mortality among sepsis patients in the ICU remain incompletely understood, with existing studies showing limitations in sample size and verification dimensions.MethodsData of ICU patients (18<age<90) who met the sepsis diagnostic criteria (Sepsis-3 definition) were extracted from the MIMIC-IV(2.0) clinical database. Patients were grouped according to the tertiles of FALC (low, medium, high); FALC was the absolute lymphocyte count in the first complete blood count upon admission to the ICU; the outcome indicator was 28-day all-cause mortality. Baseline analysis: For measurement data, normally distributed data were described as mean ± standard deviation, skewed distributed data as median (Q1-Q3), and count data as frequency (percentage). Differences between groups were tested using t-test, chi-square test, or non-parametric test. Survival analysis: KM method was used to draw survival curves, and log-rank test was used to compare differences between groups; Cox proportional hazards model was used to analyze univariate/multivariate associations, and hazard ratios (HR) and 95% confidence intervals (CI) were calculated. Non-linear verification: RCS model was used to fit the non-linear relationship between FALC and death risk, and the linear hypothesis was tested.Predictive efficacyCox regression ROC curve was used to calculate the area under the curve (AUC) to evaluate the predictive value of FALC.ResultsThe study of 10,263 sepsis patients admitted to the ICU found that FALC grouping significantly affected 28-day survival outcomes, as shown by Kaplan-Meier survival analysis and Cox regression analysis. Low FALC group having a significantly higher 28-day mortality risk compared to the medium and high groups. Restricted cubic splines verified a non-linear relationship between FALC and 28-days mortality, and the ROC curve confirmed that FALC has a certain prognostic predictive efficacy.ConclusionIn sepsis patients, lymphopenia represents a significant high-risk factor, while the first absolute lymphocyte count (FALC) stands out as a clinically meaningful indicator. It allows for precise risk stratification of patients at the time of ICU admission, thereby enabling timely immune interventions that can effectively enhance prognostic outcomes.